2010
DOI: 10.1007/s10964-010-9531-8
|View full text |Cite
|
Sign up to set email alerts
|

Special Issue Introduction: The Meaning and Measurement of Thriving: A View of the Issues

Abstract: We introduce this special issue on the foundations and functions of adolescent thriving by summarizing the developmental systems theory-based, positive youth development (PYD) perspective. The PYD perspective frames much of contemporary research about health and positive development across the adolescent period and, more specifically, frames the 4-H Study of PYD, the data set from which the empirical work in this special issue is drawn. We discuss the different ways in which the articles in this special issue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
109
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 139 publications
(119 citation statements)
references
References 49 publications
7
109
0
3
Order By: Relevance
“…The 4-H Study of PYD The 4-H Study of PYD (e.g., Lerner et al 2005Lerner et al , 2009Lerner et al , 2010Lerner et al , 2011 seeks to identify the individual and ecological relationships that may promote thriving and that, as well, may have a preventive effect in regard to risk/problem behaviors. Within the 4-H Study, thriving is seen as the growth of attributes that mark a flourishing, healthy young person, for example, the characteristics termed the ''Five Cs'' of PYD-competence, confidence, character, connection, and caring (Eccles and Gootman 2002;Lerner et al 2005;Roth and Brooks-Gunn 2003a, b).…”
Section: Introductionmentioning
confidence: 99%
“…The 4-H Study of PYD The 4-H Study of PYD (e.g., Lerner et al 2005Lerner et al , 2009Lerner et al , 2010Lerner et al , 2011 seeks to identify the individual and ecological relationships that may promote thriving and that, as well, may have a preventive effect in regard to risk/problem behaviors. Within the 4-H Study, thriving is seen as the growth of attributes that mark a flourishing, healthy young person, for example, the characteristics termed the ''Five Cs'' of PYD-competence, confidence, character, connection, and caring (Eccles and Gootman 2002;Lerner et al 2005;Roth and Brooks-Gunn 2003a, b).…”
Section: Introductionmentioning
confidence: 99%
“…One way of analyzing positive resources and development is the Positive Youth Development (PYD) theory that is based on positive psychological thinking (Lerner, 2009; see also Lerner et al, 2010). Positive psychology refers to a wide spectrum of concepts that describe positive emotions, character strengths, and positive institutions (see e.g., Seligman et al, 2005;Seligman & Csikszentmihalyi, 2000) that enable human beings' optimal, positive action (see Gable & Haidt, 2005;Linley et al, 2006).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Numerous studies have documented the relationship between a sense of meaning and purpose and well-being in adolescence (Burrow, et al, 2010;Ho et al, 2010;Kiang & Fuligni, 2010;Lerner et al, 2010;). In their study of sense of purpose in youth, Burrow et al (2010) analyzed self-report scales of 318 students and found that adolescents committed to exploring meaning and purpose during their teenage years were also more adaptive, positive, hopeful, and better able to effectively adjust to developmental (2010) reported that being able to make meaning of past life events is also positively related to self-esteem and physical and psychological health.…”
Section: Importance Of Meaning-making In Adolescencementioning
confidence: 99%